2022
DOI: 10.3390/f13101557
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Subculture Cycle, Hormone Ratio, and Carbon Source Regulates Embryonic Differentiation of Somatic Cells in Pinus koraiensis

Abstract: During somatic embryogenesis of Pinus koraiensis, the ability of the embryogenic callus to produce embryos gradually decreases with long-term proliferative culture, which seriously affects large-scale application of this technology. In this study, embryogenic calli of Korean pine 1–100 cell line were used as materials. It was found that in the 7-day subculture cycle of embryogenic calli the somatic embryogenic potential of Korean pine remained for the longer time. In comparison with a subculture cycle of 14 da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…In addition, the experimental group with a higher number of somatic embryo transitions also showed higher SOD activity, which supporting previous results. As the subculture cycle increased, SOD activity in the plants decreased significantly, which is consistent with the studies of Ren et al. (2022) .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In addition, the experimental group with a higher number of somatic embryo transitions also showed higher SOD activity, which supporting previous results. As the subculture cycle increased, SOD activity in the plants decreased significantly, which is consistent with the studies of Ren et al. (2022) .…”
Section: Discussionsupporting
confidence: 90%
“…In somatic embryogenesis of Camellia sinensis ‘Tieguanyin’, the content of endogenous IAA and ABA was found to be closely related to the development of spherical embryos and the maturation of somatic embryos ( Guo et al., 2018 ). In addition, the ratio of IAA to ABA is a crucial factor influencing somatic embryogenesis in plants ( Ren et al., 2022 ). The expression of callus embryogenicity benefits from a lower ratio of IAA: ABA ( Liang et al., 2016 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In green budwood culture, low concentration of BA at 0.5 mg/L and high concentration of 2,4-D at 2.0 mg/L required, plantlet regeneration in this study required high concentration of BA (2.0 mg/L) and slightly lower concentration of 2,4-D. This might be due to different amount of plant growth regulators and the respond to it.In addition, several researchers reported that MS medium supplemented with 0.06 mg/L NAA and 0.03 mg/L BA gave the suitable for SE induction and plant conversion rate in many plant species including Canabis sativa L. [16], Cinchona officinalis [18] and Pinus koraiensis [29]. The low level of auxin and cytokinin in the SE induction medium was sometimes responsible for the development of SE directly from the explants, implying that they did not develop through callus formation [30].…”
Section: Effect Of Types Of Explants On Ec Formation and Number Of Sesmentioning
confidence: 99%
“…Ecological and economic value may be found in the monoecious plant Pinus koraiensis , an evergreen conifer of Pinaceae with a tree height of 40 m and a breast height diameter of 1 m ( Li et al., 2022 ; Park et al., 2016 ; Ren et al., 2022 ). P. koraiensis is mostly distributed in China’s Changbai Mountains, Laoyeling Mountains, Zhangguangcailing Mountains, Xiaoxinganling Mountains and Wanda Mountains, as well as in Japan, the Far East region of Russia and the Korean Peninsula ( Aizawa et al., 2012 ; Shi et al., 2020 ; Wei et al, 2022 ; Zhang et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%